Investigative study about sources and consequences of emotional toxicity in the workplace. - Lim, Jenny Cheng Choo. (2009)
This paper uses the term 'emotional toxicity' to denote stress in the workplace to suggest that the consequences of stress are toxins which can and do cause harm. This paper deals with two constructs of emotional toxicity; its sources and consequences. Qualitative research design and methods are deployed in three areas : the data source is obtained from a compilation of verbatim interviews given by people talking about their work, a grounded theory approach was used to do the data analyse, and finally, the presentation of the findings was done using illustrative data and narrative means.